Legal Analysis of Domestic Violence Based on the Mazhab Syafi’i and Indonesian Positive Law - Muhammad Riezky Pradana Mukhtar; Misbakhul Munir AlMubarok; Budiman Mustofa (Justisi)
This research aims to examine how standards for handling domestic violence can be formed by considering the views of the Shafi'i Mazhab and positive law in Indonesia.